FUTURE TRENDS OF OIL DEMAND IN LIGHT OF COMPETITION FROM ALTERNATIVE SOURCES (World Economics and Finance Bulletin, 2022)
There is a raging debate among specialists about the importance of oil and its future role, as well as competition for oil demand in light of the presence of multiple and varied alternatives. This is because oil, according to Hubert's theory, is a depleted substance, and there are those who believe the opposite. , Because technological developments will increase exploration and thus oil reserves, and some technologies contribute to reducing oil waste during various oil operations . The research sheds light on the strategic importance of oil and its future position in the list of global energy sources and the role of alternative sources in competition and the acquisition of oil demand sources . Other non-fossil sources will also be covered, in addition to gas and coal, and the research hypothesis compatible with oil will remain at the top of the list of energy sources for the next five decades.
Keywords: competition; acquisition; compatible; fossil